Henri Duveyrier et Cheikh ‘Othmân, cartographes du Sahara - Dominique Casajus (L’Année du Maghreb)
The book published by Henri Duveyrier in 1864 under the title Tuaregs of the North included a 1/3000000 scale map which was considered for decades as the reference map of the Sahara. He had drawn it up based on three sources: his own itineraries, meticulously noted down, the routes of his predecessors, including the explorer Heinrich Barth; finally, the information provided on site by the Tuaregs and Arabs he met. The purpose of this article is to describe, through a reinterpretation of the traveler’s logs, the journey that led from his various sources – observations and testimonies – to the book that was finally published. This shows how much the author owed to local informants for their contribution, including scholar Sheikh 'Othman, who, in a way, acted as his mentor during his stay in Tuareg country. We shall also point out the signs emerging from his notes of his dialogic interactions with local informants.